Neurodevelopmental outcome of neonates with hypoglycemia in Erbil, Iraq - Sadiq, Mahmood Mohammed; Kakasur, Media Abdullah; Abdulhadi , Ahmed Mammon (Journal of Neonatal Surgery, 2025)
Background and Objectives: Neonatal hypoglycemia is a frequent metabolic disturbance that may result in long‑term neurodevelopmental impairment. This study evaluated the neurodevelopmental outcomes of neonates with hypoglycemia in Erbil, Iraq, and identified associated risk factors. Methods: A prospective observational study was conducted from January 2023 to June 2024 involving 140 neonates with hypoglycemia (blood glucose < 40 mg/dL) admitted to two tertiary hospitals. Neurodevelopmental status was assessed at 6, 12, and 18 months using the Denver II and Bayley III scales. Results: Among 140 infants (47.9% males; mean gestational age 37.75 ± 1.16 weeks; mean birth weight (BW) 2.73 ± 0.31 kg), 46 (32.9%) had normal development, 48 (34.2%) mild delay, 32 (22.9%) moderate delay, and 14 (10.0%) severe delay. Developmental delay significantly correlated with severity of hypoglycemia (p < 0.001), duration > 6 hours (95.4% of delays), low BW (<2.5 kg, p < 0.001), prematurity (<37 weeks, p = 0.006), and maternal diabetes (p < 0.001). Infants without delay had higher mean blood glucose (34.15 ± 2.22 mg/dL) and BW (2.94 ± 0.19 kg) (p < 0.001). Motor (38.3%) and language (34.0%) deficits were most common. Conclusion: Neonatal hypoglycemia, especially when severe, prolonged, or associated with maternal diabetes and low BW, significantly increases the risk of neurodevelopmental delay. Early diagnosis and vigilant glucose management are essential for neuroprotection